Characterization and evaluation of monoclonal antibodies developed for typing influenza A and influenza B viruses - H H Walls; Maurice W. Harmon; J.J. slagle; C Stocksdale; Alan P. Kendal (1986)
Monoclonal antibodies that are broadly reactive with influenza A or influenza B viruses were produced as stable reagents for typing influenza viruses. Monoclonal antibodies to influenza A were specific for either matrix protein or nucleoprotein. The antibodies to influenza B were specific for nucleoprotein or hemagglutinin protein. In an enzyme immunoassay procedure, influenza A antibodies detected H1N1, H2N2, and H3N2 influenza A virus strains collected between 1934 and 1984. Each of the influenza B antibodies detected influenza B reference viruses collected between 1940 and 1984. Pools of either influenza A or influenza B monoclonal antibodies were used to detect influenza viruses reisolated from clinical specimens in tissue culture. At 48 h after inoculation, the influenza A monoclonal antibodies detected 64% of H1N1 and 94% of H3N2 influenza A specimens, and the influenza B monoclonal antibodies detected 79% of the influenza B specimens. The results of this study suggest that the monoclonal antibodies described should provide useful diagnostic reagents for workers in virology laboratories who wish to isolate and identify influenza virus but have been unable to obtain consistent supplies of animal sera specific for influenza A or B viruses.